Five undervalued edible species inherent to autumn-winter season: nutritional composition, bioactive constituents and volatiles profile - Tamara Fukalova Fukalova (PeerJ Inc., 2021)
Background Wild edible herbs have historically been used as local nutritional and medicinal sources. These plants grow spontaneously, depending on the season. They adapt well to different edaphoclimatic conditions, generating a diversity constituent beneficial to health. They impart compounds needed in the human diet in regard to macro and micronutrients. When consumed raw, they keep their properties intact and provide health benefits. Five undervalued edible plants: Stellaria media (L.) Vill, Tropaeolum majus L., Sonchus oleraceus L., Chenopodium album L. and Diplotaxis erucoides (L.) DC are characteristic of the autumn-winter season in the Valencian coastal region and could have new sustainable agro-ecological potential for the local commercial sector. However, little information is available from the nutritional quality and bioactive composition viewpoint for these species. Concurrently, the volatiles compounds profiles describing the characteristic flavors are unknown. Methods Nutritional characteristics, bioactive compounds, and other chemical components of the fresh leaves were analyzed. In addition, the volatiles composite profile was performed. The analyzed species come from the soil reservoir; their wild growth is adjusted to the autumn season. The proximate analysis was carried out by Association of Official Analytical Chemists methods. Total antioxidants were measured as 2.2-diphenyl-1-picrylhydrzyl hydrate (DPPH) and total polyphenols content via the Folin-Ciocalteu procedure. Volatiles profile was determined by gas chromatography-mass spectrometry. The vegetative part analyzed was the tender leaves with edible potential. Results A high variability has been obtained in the composition of the species studied. The proximate analysis found a considerable content of fiber (1.22–5.4 g·100 g−1), potassium (157.7–1,250.6 mg·100 g−1), iron (0.6–2.0 mg·100 g−1), and a low caloric value (16.1–43.02 kcal·mg·100 g−1). In bioactive compounds analysis, a high level of antioxidants was highlighted (1,604.3–4,874.6 μmol·100 g−1), followed by chlorophylls. Volatiles profile revealed that the species were rich in benzenoids (33.8–89.9%) as the majority family. The pyrazines class was characteristic only in D. erucoides L. Discussion Fresh edible leaves of the undervalued plants show considerable nutritional potential and a high bioactive components level, which highlight the antioxidant capacity. Leaves of C. album L. stand out due to their higher concentration of nutritional compounds, while D. erucoides L. is noted for its higher antioxidant capacity. Aromatic descriptor of pyrazines detected in the leaves of D. erucoides L. is associated with the slightly spicy flavors that characterize this species. Results suggest that studied species could be of great relevance in introducing these five edible herbs as a source of new grown material, postulating them as healthy food ingredients with attractive flavors for the gourmet cuisine industry.